3D seismic attributes for structural mapping and enhancement of deep gold mining: a case study from the West Wits Line goldfields, South Africa. Issue 3 (1st June 2018) - Nkosi, Nomqhele Z.; Manzi, Musa S. D.; Brovko, Oleg; Durrheim, Raymond J.
Abstract : Volumetric and horizon-based seismic attributes were carried out on the 3D reflection seismic data acquired on the deep crystalline rock environments of the Witwatersrand Basin (South Africa). This study aimed at improving the delineation of minor faults that cross-cut the gold-bearing quartz pebble conglomerate horizons (termed reefs) in the complex geology of the West Wits Line (WWL) goldfield using different seismic attributes. The 3D seismic data show delineation of faults that cross-cut and displace the target horizons by tens to hundreds of metres, leading to the delineation of the ore resources in faulted areas of the mines. In particular, the ant-tracking technique has provided better stratigraphic and structural imaging in complex faulted areas, relative to conventional interpretation methods. Other improvements include more accurate mapping of the depths, dip and strike of the key seismic horizon (Roodepoort shale) using the edge detection attributes, yielding a better understanding of the interrelationship between fault activity, reef distribution and the relative chronology of tectonic events. The integration of the 3D reflection seismic data, seismic attributes and information from borehole logs and underground mapping has provided better imaging and modelling of important fault systems that might have a direct effect on mining. This information could be used for future mining planning and designs to: (1) assess and mitigate the risks posed by mining activities, and (2) improve the resource evaluation of the gold-bearing reefs in the WWL goldfield. Abstract : In this study, we use sophisticated seismic attributes to interpret the 3D reflection seismic data to: (1) assess and mitigate the risks posed by deep mining activities and (2) improve the resource evaluation of the gold-bearing quartz pebble conglomerate horizons (reefs) in the world's deepest gold mines (South Africa).